The association of physical activity and academic performance : sleep and anxiety as mediators - Anna Alexandra Petersen 2002-; Kolfinna Íris Rúnarsdóttir 2001- (2024)
Numerous studies have established a positive correlation between physical activity and academic performance. Furthermore, engaging in physical activity promotes better sleep and reduces anxiety levels, potentially leading to enhanced academic performance. Since regular physical activity positively influences sleep quality and reduces anxiety, it could subsequently impact academic performance. This study examined the relationship between physical activity and academic performance among Icelandic adolescents. Concurrently, it explored the potential mediating roles of sleep duration and anxiety levels on the relationship. The data obtained in the study was collected from the Youth in Iceland survey, conducted in 2018 by The Icelandic Centre for Social Research and Analysis. A sample of Icelandic adolescents (N = 2,000) aged 15-20 years completed a self-report questionnaire, through which the variables included in this study were measured. The results demonstrated a significant positive correlation between physical activity and academic performance. Furthermore, a significant mediation effect of sleep and anxiety on the relationship was established. The independent mediation effect of anxiety on the relationship was found to be significant. However, the independent mediation effect of sleep on the relationship was insignificant. Further investigation is suggested, particularly incorporating objective measurement methods and a longitudinal design. Keywords: Academic performance, adolescents, anxiety, mediation, physical activity, sleep Fjölmargar rannsóknir hafa sýnt fram á jákvæð tengsl hreyfingar og námsárangurs. Jafnframt hafa rannsóknir gefið til kynna að regluleg hreyfing getur bætt svefn og dregið úr kvíða. Þar sem regluleg hreyfing hefur jákvæð áhrif á svefn og neikvæð áhrif á kvíða, gæti það jafnframt haft áhrif á námsárangur. Þessi rannsókn skoðaði samband hreyfingar og námsárangurs íslenskra framhaldsskólanema og hvort svefn og kvíði miðli sambandinu. Rannsóknargögn voru fengin úr skólarannsókninni Ungt ...